Religious Moderation in Responding to Gender, Human Rights, and Ecology Issues: An Examination in the Perspective of Contemporary Islamic Studies - Asmiati, Rini; Suprehatin, Yulia; Kamar, Fahmi; Kamaruddin, Kamaruddin; Khojir, Khojir; Nursalim, Eko (International Journal on Advanced Science, Education, and Religion, 2025)
Religious moderation is a fundamental concept in Islamic teachings that prioritizes the principles of balance, justice and tolerance, both in religious and social life. In facing the challenges of globalization and the dynamics of modern times such as radicalism, gender inequality, human rights violations, and environmental crises, a moderate approach to religion is an important strategy in maintaining harmony, harmony, and diversity. This research aims to explore the relevance of religious moderation in the contemporary social context by highlighting the importance of reinterpreting Islamic teachings based on the values of gender justice, respect for human rights, and rejection of all forms of violence in the name of religion. Through a study of contemporary Islamic thought and the maqashid sharia approach (the main purpose of sharia), this study reveals that religious moderation can be used as a foundation in the formation of character education, the development of inclusive public policies, and the strengthening of constructive interfaith dialog. This approach not only plays a role in overcoming social polarization, but also in building a just, equal and sustainable society. Thus, religious moderation in Islam is not just a middle-of-the-road attitude, but an active commitment to the values of civilization, social justice and peace. The findings of this study confirm that a moderate and contextualized Islam is able to contribute to a just and sustainable society.